Believing and Doubting as Hermeneutic Method: Reading and Teaching Paradise Lost - Sheridan Blau (Journal of the Assembly for Expanded Perspectives on Learning, 2009)
Using a variation on Peter Elbow's believing game, I help students discover the degree to which Milton in Paradise Lost succeeds in his explicit attempt to justify God's ways to man and in that success also offers us an account of human happiness and misery that is psychologically sophisticated, spiritually illuminating, entirely rational, and supremely wise as a guide to living a humanly satisfying life. Such an approach to Paradise Lost also fosters an experience of the text through which many students undergo a modern version of the spiritual transformation and enlightenment that Milton explicitly aimed to make possible for readers of his epic.